Odpowiedź :
5x + 3y = 0
-x-2y = 7 /*5
5x+3y=0
-5x-10y=35
5x+3y+-5x-10y=35
5x+3y=0
-7y=35 / : (-7)
5x+3y=0
y= -5
5x+3*(-5)=0
y = -5
5x - 15 = 0 / +15
y = -5
5x = 15 / :5
y= -5
x= 3
-x-2y = 7 /*5
5x+3y=0
-5x-10y=35
5x+3y+-5x-10y=35
5x+3y=0
-7y=35 / : (-7)
5x+3y=0
y= -5
5x+3*(-5)=0
y = -5
5x - 15 = 0 / +15
y = -5
5x = 15 / :5
y= -5
x= 3
5x+3y=0
-x-2y=7 / ×5
5x+3y=0
-5x-10y=35
(5x z -5x się redukuje)
-7y=35 /÷ (-7)
y=-5
aby wyliczyć x trzeba podstawić pod równanie
5x+3×(-5)=0
5x-15=0
5x=0+15
5x=15 /÷5
x=3
y=-5
x=3
-x-2y=7 / ×5
5x+3y=0
-5x-10y=35
(5x z -5x się redukuje)
-7y=35 /÷ (-7)
y=-5
aby wyliczyć x trzeba podstawić pod równanie
5x+3×(-5)=0
5x-15=0
5x=0+15
5x=15 /÷5
x=3
y=-5
x=3